The Effects of Bedrest on Circadian Changes in Hemostasis - Rosenfeld, Brian A; Faraday, Nauder; Campbell, David; Sakima, Neal; Bell, William (Thrombosis and Haemostasis, 1994)
Venous stasis occurs when people are at bedrest, because of altered venous flow characteristics. This is commonly believed to be one etiology behind the development of deep venous thrombosis (DVT). The hemostatic effects of bedrest and their possible role in DVT development have not been fully examined. We hypothesized that bedrest would lead to increases in hemostatic function and that these increases could be important in the development of DVT.Twelve non-smoking volunteers were studied during supine positioning for 36 hours. Platelet reactivity and plasma concentrations of fibrinogen, a2-antiplasmin, plasminogen, thromboxane (32, plasminogen activator inhibitor-1, tissue plasminogen activator and neuroendocrine hormones (cortisol, epinephrine and norepinephrine) were measured at 8:00 a.m., 10:00 a.m., 4:00 p.m. and 8:00 a.m.Cortisol demonstrated an early morning increase while catecholamines were unchanged throughout. Fibrinogen, a2-antiplasmin, plasminogen and platelet reactivity were no different at any time point. Fibrinolytic proteins changed over time, manifested by decreased PAI-1 antigen and activity levels at 24 h.Based upon the parameters measured, bedrest causes no increase in hemostatic function. In fact, bedrest causes the potential for enhanced fibrinolysis, that differs from that previously reported for normal activity over 24 h. This may represent a protective mechanism to counter the effects of stasis from bedrest.